2018
DOI: 10.1177/2158244018775466
|View full text |Cite
|
Sign up to set email alerts
|

Why Is Parental Involvement in Children’s Mathematics Learning Hard? Parental Perspectives on Their Role Supporting Children’s Learning

Abstract: This article focuses on parents' experiences and practices supporting children's mathematics learning. We employ a conceptual framework that makes a distinction between school-centered and parent-centered approaches to parental involvement in children's learning. We review literature showing that aspects of both school-centered and parent-centered approaches can be problematic, and explore this further in a group interview study. Group interviews were conducted with parents of children in 16 primary schools in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 30 publications
6
56
0
6
Order By: Relevance
“…They blame the new methodological approaches that are quite different from those they remember from the time when they were students. These difficulties felt by parents when they try to help their children with their mathematics homework are also pointed out in other studies (Jay et al, 2018).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…They blame the new methodological approaches that are quite different from those they remember from the time when they were students. These difficulties felt by parents when they try to help their children with their mathematics homework are also pointed out in other studies (Jay et al, 2018).…”
Section: Introductionsupporting
confidence: 58%
“…In these authors' perspective, parents' involvement in their children's education plays an important role and has a strong impact, in their opinion, both on the cognitive development of the child and on his school performance and achievement. Consequently, the majority of parents do their best to be involved and to help their children with the tasks they were assigned by their math teachers, even though, as stated by Menezes et al (2016) and Jay et al (2018), they sometimes find it difficult to keep that commitment because of the new contents that are being taught and of the methodologies that are currently being used and that are unlike everything they experienced when they were students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite awareness that arithmetic fluency, including knowledge and retrieval of multiplication facts, may be useful for children's mathematics thinking and learning, it is not clear that schools have good knowledge of methods for supporting children to learn such facts. Previous work has shown that such learning is often "out-sourced" to parents, who themselves feel unable to effectively support their children's mathematics learning (Jay et al, 2018). Verguts and Fias (2005) propose a connectionist model of automaticity of multiplication fact retrieval.…”
Section: Arithmetic Fluencymentioning
confidence: 99%
“…Orang tua yang kurang melibatkan diri dalam pendidikan anaknya tersebut disebabkan oleh berbagai macam faktor. Salah satu diantaranya yaitu sibuknya aktivitas atau pekerjaan orang tua, sehingga menyebabkan kurangnya keterlibatan yang diberikan oleh orang tua kepada anaknya (Jay, Rose, & Simmons, 2018). Kurangnya keterlibatan orang tua tersebut dapat menyebakan anak-anak menjadi malas, acuh tak acuh, dan kurangnya motivasi atau minat belajar (Silinskas & Kikas, 2019).…”
Section: Introductionunclassified